Symbolic representations of money among Igbo traders in Ladipo international market, Lagos (2019)
This article is a product of an ethnographic study of Ladipo International Market, Lagos Nigeria, focusing on symbolic representations of money among the Igbo traders in the space. Interactions amongst the traders, and with their clients have led to the development of form of relationships with shared interests and meanings. These, coupled with the organisational culture of the market, contribute to its peculiarity, and are critical to successful business transactions. This article identifies the practices, ideas and objects the traders symbolically construct as money, and how the constructs mediate intra- and inter- group relations, and finally identifies the patterns in the traders' behaviours and social relationships when money mediates exchanges, and how symbolic meanings further reshape social relationships. The focus is not only to understand the observable phenomenon, but also to unveil the meanings that underlay the practice. The study adopted ethnographic approach, using such methods as in-depth interviews, participant observation and life history. Relevant documents were also consulted. Collected data were analysed qualitatively. The study establishes that 'importation', 'imara anya ahia' (knowledge of trading skills), 'containers' and exotic cars are symbols of money. Relationships are structured along the social categories engendered by these symbols on the one hand, and 'Master' and 'nwaboy' (apprentice) line on the other hand, with each further invoking relational patterns and meanings.